Singularities of amplitude and phase measuring in problems of a spatially distributed object diagnostics (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
Singularities of development of new methods and the fast broadband space diversity systems of impulse amplitude and phase measuring and spectrometry, capable to measure temporary and frequency parameters  of spatially distributed dynamic objects of various physical nature are considered. Information about practical em-bodying such systems and their technical features are presented.